PENGARUH DAYA TARIK STADION SEPAKBOLA DAN AKOMODASI atau FASILITAS TERHADAP MINAT WISATAWAN DI STADION MAGUWOHARJO SLEMAN - Arnol Rudiati Toineno; An wani (STIE Pariwisata API Yogyakarta, 2018)
This study is intended to find out how much influence the attractiveness of the Maguwoharjo Football Stadium is as well as the accommodation or facilities to the interest of tourists or spectators who come to the Maguwoharjo Sleman football stadium. In this study using multiple linear regression analysis tools using survey methods with questionnaires as a data collection tool and involving 100 respondents who are all tourists or viewers who came and who had come to watch the match at the Maguwoharjo Sleman Football Stadium with the age range 17 to 50 years. The sampling technique used purposive sampling. The results of this study indicate that all independent variables (Maguwoharjo Football Stadium Attractiveness and Accommodation or Facilities) have a positive and significant effect on the dependent variable (Tourist or Audience Interest) who come to the Maguwoharjo Sleman Football Stadium. This is proven to be variable. The attraction of Maguwoharjo Football Stadium and Accommodation or Facilities has a significance value smaller than alpha 0.05, this means that each independent variable has a significant effect on Tourist or Audience Interest. The input of this research is to provide insight and knowledge in the management of the Football stadium as one of the tourist attractions, so that it can be used as a consideration in making the decision to build the Maguwoharjo Sleman Football Stadium in terms of intersting many tourists or spectators. In addition, this research can be a reference material for further research related to sports tourism.Keywords: Attraction, Influence, Accommodation, Tourists, Football Stadi